Interactive Machine Anatomy Explorer using Augmented Reality - Samsul Kamal, Azhari; Mad Sahar, Nan (Evolution in Electrical and Electronic Engineering, 2021)
The wide potential of Augmented Reality (AR) for future applications has to gain the interest of the big companies to implement AR technologies in their production. AR have a various function in especially for educational, maintenance, design and training purpose. The importance of AR in the industry is to reduce the errors in maintenance and to increase the skill of the new workers with less involvement of the experienced workers in line with the industry revolution 4.0. The purpose of this project is to design and develop an augmented reality (AR) based application that allows users to be able to learn and understand the anatomy of a machine, and to measure the application usability and receptions. The design and developing process will be using the Unity3d engine and Vuforia SDK as the main software. To measure the usability and of the developed application its reception, a survey has been distributed to the students of the Universiti Tun Hussein Onn Malaysia (UTHM). The application developed is able to display the anatomy of the worm gear reduction by using a quick response (QR) code as the image target. The Interactive Machine Anatomy Explorer have 85% performance accuracy to detect the QR code. The application is able to detect the QR code with minimal light. The suggested distance to obtain the best result of the worm gear reducer anatomy is between 45 cm to 90 cm. From the survey done, the majority of the respondents (67%) agree that they will use the AR application that is able to show the machine’s components anywhere and anytime and 88% of the respondents think that it will reduce the time taken for them to understand the components detailed. These results show that AR involvement in the education process could be implemented to facilitate users in understanding the machine’s components better.